QAWA’ID USHULIYYAH TASYRI’IYYAH SEBAGAI PRINSIP DASAR DALAM MEMAHAMI TEKS AL-QUR’AN DAN HADIS - Muhammad Itsbatul Haq (Qur'an and Hadith Academic Society, 2017)
The sacredness of texts of Islamic law sources, Qur'an and Sunna, as holy texts and the ability of both in facing every evolving dynamics of human life really get the endurance examination today. On the one side, strict rules are necessary to keep the texts holy. At the same time, the rule could not limit the creativity of human thought which from the beginning was presented as God’s greatest gift for human beings. Qawa>’id Usu>liyyah Tasyri>’iyyah in discourse of Usu>l al-Fiqh comes in order to maintain holiness of the texts and fulfill human needs at the same time.